Cr(VI) removal from aqueous systems using pyrite as the reducing agent: Batch, spectroscopic and column experiments - Kantar, Cetin; Ari, Cihan; Keskin, Selda; Dogaroglu, Zeynep Gorkem; Karadeniz, Aykut; Alten, Akin (ELSEVIER SCIENCE BV, 2015)
Laboratory batch and column experiments, in conjunction with geochemical calculations and spectroscopic analysis, were performed to better understand reaction mechanisms and kinetics associated with Cr(VI) removal from aqueous systems using pyrite as the reactive material under both static and dynamic flow conditions similar to those observed in in situ permeable reactive barriers (PRBs). The X-ray photoelectron spectroscopy (XPS) and geochemical calculations suggest that the Cr(VI) removal by pyrite occurred due to the reduction of Cr(VI) to Cr(III), coupled with the oxidation of Fe(II) to Fe(III) and S-2(2-) to SO42- at the pyrite surface. Zeta potential measurements indicate that although the pyrite surface was negatively charged under a wide pH range in the absence of Cr(VI), it behaved more like a metal oxide surface with the surface potential shifting from positive to negative values at pH values >pH 6 in the presence of Cr(VI). Batch experiments show that increasing solution pH led to a significant decrease in Cr(VI) removal. The decrease in Cr(VI) removal at high Cr(VI) concentrations and pH values can be explained through the precipitation of sparingly soluble Cr(OH)(3(s)), Fe(OH)(3(s)) and Fe(III)-Cr(III) (oxy) hydroxides onto pyrite surface which may, then, lead to surface passivation for further Cr(VI) reduction. Batch results also suggest that the reaction kinetics follow a first order model with rate constants decreasing with increasing solution pH, indicating proton consumption during Cr(VI) reducdon by pyrite. Column experiments indicate that nearly 100% of total Fe in the column effluent was in the form of Fe(II) species with a [[SO42-]/[Fe2+]] stoichiometric ratio of 2.04, indicating that the reduction of Cr(VI) by pyrite produced about 2 mol of sulfate per mole of Fe (II) release under excess surface sites relative to Cr(VI) concentration. Column experiments provide further evidence on the accumulation of oxidation products which consequently led to a significant pressure build up in pyrite packed columns over time. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Pyrite; Permeable reactive barrier (PRB); Reduction; Sorption; Chromium; Treatment; Oxidation; HEXAVALENT CHROMIUM; SURFACE; REMEDIATION; ADSORPTION; STABILIZATION; KINETICS; CR(III); Environmental Sciences & Ecology; Geology; Water Resources